2019
DOI: 10.1186/s12885-019-6003-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning enables detection of early-stage colorectal cancer by whole-genome sequencing of plasma cell-free DNA

Abstract: Background Blood-based methods using cell-free DNA (cfDNA) are under development as an alternative to existing screening tests. However, early-stage detection of cancer using tumor-derived cfDNA has proven challenging because of the small proportion of cfDNA derived from tumor tissue in early-stage disease. A machine learning approach to discover signatures in cfDNA, potentially reflective of both tumor and non-tumor contributions, may represent a promising direction for the early detection of can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 35 publications
3
79
0
Order By: Relevance
“…Previous ML-based studies performed in ccfDNA materials have also shown promising results in CRC. Wan et al built an ML-based model for the early detection of CRC with an AUC of 0.92 (95% CI: 0.91–0.93) [ 76 ], while Luo et al constructed a predictive model that accurately discriminated CRC patients from healthy individuals (AUC: 0.96) [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous ML-based studies performed in ccfDNA materials have also shown promising results in CRC. Wan et al built an ML-based model for the early detection of CRC with an AUC of 0.92 (95% CI: 0.91–0.93) [ 76 ], while Luo et al constructed a predictive model that accurately discriminated CRC patients from healthy individuals (AUC: 0.96) [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Putcha et al performed a study on a ML-based approach to discover signatures in cell-free DNA to potentially improve the detection of colorectal cancer (NCT03688906; [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parallel analysis with RNAseq and MNase-seq of the matched primary tumor and blood samples may facilitate the discovery of correlations between cfDNA nucleosome positioning and relevant gene expression with the nucleosome occupancy of the genes. cfDNA contains DNA from both normal and tumor tissues in patients with breast cancer, and studies have found cfDNA derived from tissue-specific and tumor-specific open chromatin regions (NFR or NDR) 20 , 21 . Because the fractions of tumor- and non-tumor cfDNA vary among different patients 4 , a limitation of our study is that we failed to consider the two fractions of normal and tumor DNA.…”
Section: Discussionmentioning
confidence: 99%